Filipino (Tagalog) phrasebook & dictionary - O'Connell, Lauren (Lonely Planet, 2020)
Lonely Planet Filipino (Tagalog) Phrasebook & Dictionary is your handy passport to culturally enriching travels with the most relevant and useful Filipino (Tagalog) phrases and vocabulary for all your travel needs. Chat with locals and navigate menus; all with your trusted travel companion. With language tools in your back pocket, you can truly get to the heart of wherever you go, so begin your journey now!